2017
DOI: 10.1089/jwh.2017.6389
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Sedentary Behaviors Among Lesbian, Bisexual, and Heterosexual Women: Findings from the Nurses' Health Study II

Abstract: Interventions promoting less sitting time among LB women may be warranted. Additionally, findings highlight need for more research into other modifiable factors besides PA, such as minority stress or disordered eating behaviors that may contribute to greater obesity among LB women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…41,44,46,48,[51][52][53] However, a recent study found that sexual minority women reported higher rates of certain types of physical activity (both aerobic and strengthening exercises). 54 In addition, sexual minority women in that study also reported higher rates of sedentary behaviors (including average number of hours sitting per week) relative to heterosexual women. 54 The conflicting evidence regarding sexual orientation differences in physical activity and sedentary behaviors warrants further research in this area.…”
Section: Discussionmentioning
confidence: 72%
“…41,44,46,48,[51][52][53] However, a recent study found that sexual minority women reported higher rates of certain types of physical activity (both aerobic and strengthening exercises). 54 In addition, sexual minority women in that study also reported higher rates of sedentary behaviors (including average number of hours sitting per week) relative to heterosexual women. 54 The conflicting evidence regarding sexual orientation differences in physical activity and sedentary behaviors warrants further research in this area.…”
Section: Discussionmentioning
confidence: 72%
“…Although most studies indicate there are no physical activity differences (Blosnich et al, 2014; Case et al, 2004; Fredriksen-Goldsen et al, 2013a; Garland-Forshee et al, 2014; Hatzenbuehler et al, 2013; Hatzenbuehler, Slopen, et al, 2014; Matthews & Lee, 2014), a small number of studies suggest sexual minority women have lower rates of physical activity compared to heterosexual women (Everett & Mollborn, 2013; Herrick & Duncan, 2018). However, a recent study found sexual minority women had higher rates of aerobic activity but also reported more sedentary behaviors than heterosexual women (VanKim, Bryn, Hee-Jin, & Corliss, 2017). Moreover, several studies assert sexual minority women demonstrate similar (Dilley, Wynkoop Simmons, Boysun, Pizacani, & Stark, 2010; Matthews & Lee, 2014) or worse diet quality (Minnis et al, 2015; Roberts et al, 2003; Valanis et al, 2000) compared to heterosexual women.…”
Section: Discussionmentioning
confidence: 99%
“…Health during cancer survivorship is conditional on maintaining a healthy weight and participating in healthy behaviors. In general, lesbian women have higher rates of obesity 6 and LBW have higher rates of sedentary behavior, 23 which are risks for cancer 24 and medical comorbidities. 25 These disparate risks have not been demonstrated in cancer survivors.…”
Section: Introductionmentioning
confidence: 99%